Structures and Models Formation of Scientific Competencies of Students in the Process of Continuous Vocational Education - Somova, Yuliya; Gladysheva, Maria; Sychugov, Dmitriy; Parfiryev, Kirill; Kapustina, Nadezhda; Anichkina, Olga; Anichkina, Olga; Kuznetsova, Elena; Kuchinskaya, Elena (International Journal of Psychosocial Rehabilitation, 2019)
This article presents the results of the study, which was conducted on the basis of Nosov Magnitogorsk State Technical University. The theoretical foundations of the formation of research competencies of students in the process of continuing professional education are outlined. In the process of conducting experimental work, a model was developed for the formation of students' research competencies, the requirements for the development of which are presented in the article. The pedagogical conditions for the effective formation of students' research competencies, the stages of continuing education are given and thoroughly substantiated. The proposed methodology was developed taking into account the selected principles and levels of research competencies of students, given in the article and corresponds to different stages of training. At the same time, the methodology for the formation of research competencies of students in the process of continuous professional education has a certain structure: the goal, the participants (teachers and students), the learning process in the NGO process and the result. Studies show that distance learning is of the greatest interest for professional development. Therefore, the article pays special attention to distance learning and innovative teaching methods that affect the final result of the experiment, which is given in the form of tabular data.